Nickel induces hepatotoxicity by mitochondrial biogenesis, mitochondrial dynamics, and mitophagy dysfunction. Issue 5 (16th February 2023) - Guo, Hongrui; Wei, Ling; Wang, Yihan; Cui, Hengmin; Deng, Huidan; Zhu, Yanqiu; Deng, Junliang; Geng, Yi; Ouyang, Ping; Lai, Weiming; Du, Zongjun; Ni, Xueqin; et al.
Abstract: Nickel (Ni) is an important and widely hazardous chemical industrial waste. Excessive Ni exposure could cause multi‐organs toxicity in human and animals. Liver is the major target organ of Ni accumulation and toxicity, however, the precise mechanism is still unclear. In this study, nickel chloride (NiCl2 )‐treatment induced hepatic histopathological changes in the mice, and, transmission electron microscopy results showed mitochondrial swollen and deformed of hepatocyte. Next, the mitochondrial damages including mitochondrial biogenesis, mitochondrial dynamics, and mitophagy were measured after NiCl2 administration. The results showed that NiCl2 suppressed mitochondrial biogenesis by decreasing PGC‐1α, TFAM, and NRF1 protein and mRNA expression levels. Meanwhile, the proteins involved in mitochondrial fusion were reduced by NiCl2, such as Mfn1 and Mfn2, however, mitochondrial fission proteins Drip1 and Fis1 were significantly increased. The up‐regulation of mitochondrial p62 and LC3II expression indicated that NiCl2 increased mitophagy in the liver. Moreover, the receptor‐mediated mitophagy and ubiquitin (Ub)‐dependent mitophagy were detected. NiCl2 promoted PINK1 accumulation and Parkin recruitment on mitochondria. And, the receptor proteins of mitophagy Bnip3 and FUNDC1 were increased in the NiCl2 ‐treated mice liver. Overall, these results show that NiCl2 could induce mitochondria damage in the liver of mice, and, dysfunction of mitochondrial biogenesis, mitochondrial dynamics and mitophagy involved in the molecular mechanism of NiCl2 ‐induced hepatotoxicity.